Evaluation of Teacher Performance in Implementing the Independent Curriculum at SMP Negeri 12 Tidore Islands City - Samili, Asnita Ode; Ibrahim, Fitriana; Hasim, Jainudin; Muhamad, Ardiana; Sabtu, Rasmita; Adjam, Syarifudin; Apling, Mujais (Peneliti.net, 2023)
This research aims to provide an overview of teacher performance evaluations in implementing the Independent Curriculum at SMP Negeri 12 Tidore Islands City. The approach used in this research is a qualitative descriptive approach. The population of this study were teachers and school principals. The research results show that teachers have very good understanding and insight in understanding the concepts and content of the Merdeka Curriculum. The teacher's ability to design lesson plans is good, in the Teaching and Learning Process, the class teacher has good ability to use a scientific approach and create learning that is contextual and has an integrated character, the teacher is able to design assessment signs to determine the type of authentic assessment that will be used